INTRODUCTION TO THE TEACHING OF SOCIAL STUDIES IN JUNIOR SECONDARY SCHOOL - Bello, Muhinat B. (Sokoto Educational Review, 2020)
An interdisciplinary approach to solving societal problems is the root of subject social studies. It is a subject that borrow its ideas (content) from the original social sciences, but with the view of integrating them as one whole in order to serve the aim for which it was set. In order to achieve its aims, general objectives and teaching methods have been discussed. Teachers need not to teach or handle the subject as any of the single social sciences. But to teach or handle it using integrated approach. That is the focal point of this work. The paper tries to define the concept social studies and identify some methods that can be adopted in the teaching of the subject in our junior secondary schools in order to achieve it aims. The objectives of social studies were identified, alongside with some qualities which a social studies teacher must possess in order to be able to handle the subject effectively.